Top Answer

It can be raised to any power.

It can be raised to any power.

It can be raised to any power.

It can be raised to any power.

🙏

0🤨

0😮

0😂

0Loading...

Remember to factor out the GCF of the coefficients if there is one. A perfect square binomial will always follow the pattern a squared plus or minus 2ab plus b squared. If it's plus 2ab, that factors to (a + b)(a + b) If it's minus 2ab, that factors to (a - b)(a - b)

Consider a binomial (a+b). The cube of the binomial is given as =(a+b)3 =a3 + 3a2b + 3ab2 + b3.

To calculate the cube of a binomial, you can multiply the binomial with itself first (to get the square), then multiply the square with the original binomial (to get the cube). Since cubing a binomial is quite common, you can also use the formula: (a+b)3 = a3 + 3a2b + 3ab2 + b3 ... replacing "a" and "b" by the parts of your binomial, and doing the calculations (raising to the third power, for example).

k can be 2 or -2. A binomial squared is: (a + b)² = a² + 2ab + b² Given x² - 5kx + 25 = (a + b)² = a² + 2ab + b² we find: a² = x² → a = ±x 2ab = -5kx b² = 25 → b = ±5 If we let a = x, then: 2ab = 2xb = -5kx → 2 × ±5 = -5k → k = ±2 If k = 2 then the binomial is (x - 5)² If k = -2 then the binomial is (x + 5)² To be complete if a = -x, then: If k = 2 then the binomial is (-x + 5)² If k = -2 then the binomial is (-x - 5)² which are the negatives of the binomials being squared.

(a3 + b3)/(a + b) = (a + b)*(a2 - ab + b2)/(a + b) = (a2 - ab + b2)

You write it in superscore, such as b25 or B raised to the 25th power

#include <math.h> double a, b, result; result = pow (a, b);

10-1 = 1/10 A number raised to a negative power is equal to the reciprocal of the number raised to the power. So a-b = (1/a)b = 1/ab

(a^2 - b^2) = (a - b)(a + b)

The question cannot be answered because the powers of a and b, at the start of the expression are not specified.

a3+b3

It's pow from math.h

Using the symbol "^" for power: a^(-b) = 1 / (a^b) and: a^b = 1 / (a^(-b)) In words: raising a number to a negative power is the reciprocal of the same number, raised to the corresponding positive power (the additive inverse).

The degree of a polynomial function is the highest power any single term is raised to. For example, (5a - 2b^2) is a second degree function because the "b^2" is raised to the second power and the "a" is only raised to the (implied) first power. For (24xy-xy^3 + x^2) it is a third degree polynomial because the highest power is the cube of -xy.

(a-b) (a+b) = a2+b2

We often come across the algebraic identity (a + b)2 = a2 + 2ab + b2. In expansions of smaller powers of a binomial expressions, it may be easy to actually calculate by working out the actual product. But with higher powers the work becomes very cumbersome.The binomial expansion theorem is a ready made formula to find the expansion of higher powers of a binomial expression.Let ( a + b) be a general binomial expression. The binomial expansion theorem states that if the expression is raised to the power of a positive integer n, then,(a + b)n = nC0an + nC1an-1 b+ nC2an-2 b2+ + nC3an-3 b3+ ………+ nCn-1abn-1+ + nCnbnThe coefficients in each term are called as binomial coefficients and are represented in combination formula. In general the value of the coefficientnCr = n!r!(n-r)!It may be interesting to note that there is a pattern in the binomial expansion, related to the binomial coefficients. The binomial coefficients at the same position from either end are equal. That is,nC0 = nCn nC1 = nCn-1 nC2 = nCn-2 and so on.The advantage of the binomial expansion theorem is any term in between can be figured out without even actually expanding.Since in the binomial expansion the exponent of b is 0 in the first term, the general term, term is defined as the (r+1)th b term and is given by Tr+1 = nCran-rbrThe middle term of a binomial expansion is [(n/2) + 1]th term if n is even. If n is odd, then terewill be two middle terms which are [(n+1)/2]th and [(n+3)/2]th terms.

You can do it simpler just by using preprocessor directive#include void main(){int a, b;cout cin >> a;cout cin >> b;cout }But if you know that and you still want to use a loop check following out.//some headfiles herevoid main(){int a, b, result;cout cin >> a;result = a;cout cin >> b;for (int i =1; i {result*=a;}cout }

The special products include: difference of the two same terms square of a binomial cube of a binomial square of a multinomial (a+b) (a^2-ab+b^2) (a-b) (a^2+ab+b^2)

17 = 23 + 32

2a2b2+3a2b2-5abc

It is a trinomial.The square of (a + b)^2 is a^2 + 2ab + b^2.

For example, 10 to the power -2 is defined as being the same as 1 divide by (10 to the power 2).Defining it this way ensures that many common rules for exponents continue being valid for all numbers, positive or negative - for example, (x to the power a) times (x to the power b) = x to the power (a + b).

If written without parentheses, it means that only "b" is raised to the second power. Then you multiply the result by "a".

If you mean: b squared+b+25 then the given quadratic expression can't be factored because its discriminant is less than zero.

Expansion of the Binomial a+b